2014
DOI: 10.1002/anie.201403402
|View full text |Cite
|
Sign up to set email alerts
|

Decay of Iron(V) Nitride Complexes By a NN Bond‐Coupling Reaction in Solution: A Combined Spectroscopic and Theoretical Analysis

Abstract: Cryogenically trapped Fe(V) nitride complexes with cyclam-based ligands were found to decay by bimolecular reactions, forming exclusively Fe(II) compounds. Characterization of educts and products by Mössbauer spectroscopy, mass spectrometry, and spectroscopy-oriented DFT calculations showed that the reaction mechanism is reductive nitride coupling and release of dinitrogen (2 Fe(V)≡N→Fe(II)-N=N-Fe(II)→2 Fe(II)+N2). The reaction pathways, representing an "inverse" of the Haber-Bosch reaction, were computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 44 publications
10
44
0
1
Order By: Relevance
“…The oxidation‐initiated reduction of 1 → 2 or 1 → 3 resulted in loss of nitride and subsequent 3e − metal reduction via an intermediate 1 + to Mn III ( 2 or 3 ). As was observed in other systems, such metal‐nitride reduction is typically accompanied by N 2 generation ,. To unambiguously confirm this herein, we isotopically enriched the nitride in 1 to 1 ‐ 15 N by using 15 NH 3 in the initial synthesis .…”
Section: Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…The oxidation‐initiated reduction of 1 → 2 or 1 → 3 resulted in loss of nitride and subsequent 3e − metal reduction via an intermediate 1 + to Mn III ( 2 or 3 ). As was observed in other systems, such metal‐nitride reduction is typically accompanied by N 2 generation ,. To unambiguously confirm this herein, we isotopically enriched the nitride in 1 to 1 ‐ 15 N by using 15 NH 3 in the initial synthesis .…”
Section: Methodssupporting
confidence: 79%
“…For the latter N−N bond‐formation pathways, intermediate metal‐nitride coupling ( B → C )—either through proposed bimolecular nitridyl (M≡N⋅) or nucleophilic (M≡N δ − )+electrophilic (M≡N δ + ) coupling (Scheme , bottom)—is proposed as the main pathway to μ‐N 2 or N 2 formation. Other nitrides, generated by N‐atom transfer chemistry (e.g., N 3 − photolysis), have also shown similar coupling behavior ,. Although significant progress has been made towards NH 3 oxidation to various products ( B , C , D ), closing the cycle in a fully catalytic or pseudo‐catalytic “synthetic” cycle, is rare.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the iron(V)‐nitrido complexes with four‐fold symmetry are rather reactive. Upon melting a frozen solution of [Fe V (N)(Cyclam‐ac)] + , facile N−N bond coupling takes place, leading to a ferrous compound and release of N 2 , which hampers full manifestation of its intrinsic reactivity toward organic substrates. Therefore, the reactivity of iron‐nitrido complexes with four‐fold symmetry has to be investigated in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Initially,m ost iron nitrides were successfully prepared in frozen solutions, [17][18][19] which indicated that as olid matrix and low temperatures were required for their generation. [19,20] However,u ltrafast experiments have recently shown the formation of iron nitrides at room temperature. [21][22][23] Herein, we report the photodissociation of iron(III) azides studied at the molecular level by ion spectroscopy using different temperatures (3-310 K).…”
mentioning
confidence: 99%